Empirical Exploration of TPB Extention on Savings Adoption by Indonesian Gen-Z in Sharia Banking - Ali Hanafiah; Dwyliego septo wicaksono; Fauziah Sh. Ahmad; Dudi Permana; Mas Wahyu Wibowo (International Journal of Asian Business and Management, 2024)
Indonesia operates a dual financial system comprising conventional and sharia finance. As the world's largest Muslim-majority country, the demand for sharia-compliant banking services is rising, driven by the prohibition of riba and the principles of Islamic finance. The establishment of Bank Syariah Indonesia (BSI) in 2021, following a merger of three state-owned sharia banks, underscores the nation's commitment to expanding sharia banking. This study investigates the influence of electronic word of mouth (eWOM) and religiosity on saving intentions among Generation Z customers at BSI. Data were collected from 231 respondents using an online questionnaire with screening questions. The findings reveal that EWOM significantly impacts saving intentions, highlighting the importance of digital interactions in influencing consumer behavior. While religiosity was positively correlated with saving intentions, it was not a significant determinant, suggesting that practical factors such as service quality and trust may outweigh religious considerations. These results contribute to the literature on consumer behavior in sharia banking and provide actionable insights for developing targeted marketing strategies to enhance savings adoption among younger demographics in Indonesia. This research highlights the evolving dynamics of consumer behavior of GenZ in the context of sharia banking’s growing digital transformation